Increasing the energy efficiency of cranes by improving control systems - Strelkov, Maksym; Turlakova, Natalya (My University, 2023)
The thesis is devoted to the development of the innovative strategy for energy efficiency increasing The goal of the research work is searching and testing control systems for hoisting cranes. It is a very important theme in Ukraine and even all over the world. Natural resources are limited, so humanity must realize how to use them more effectively. In order to ensure maximum effect the practical experience should be combined with the theoretical research.
Keywords: hoisting cranes; energy efficiency; energy-saving frequency converters; gear motors; control equipment